DEVELOPMENT OF MATHEMATICAL LEARNING DEVICES BASED ON CONTEXTUAL LEARNING ON THE MAIN MATERIAL OF THE SET - Elsa Despriana; Astri Wahyuni (Mathematics Research and Education Journal, 2020)
The research aimed to produce a mathematical learning device based on contextual learning. This research uses the ADDIE model, which consists of 4 stages: the Analysis stage, the Design stage, the Development stage, and the Evaluation stage. The researcher did not use the Implementation (trial) stage in the ADDIE model because school learning in the 2019/2020 school year was carried out online. The data collection technique used a non-test technique, namely by using a validation sheet as a data collection instrument which was given to 4 validators consisting of 2 FKIP UIR lecturers and two mathematics teachers at SMP Negeri 8 Pekanbaru. The data analysis technique used is the quantitative descriptive analysis technique of ratio data. The results showed that the feasibility of learning tools in lesson plans had an average of 88.48% for the four validators. For LKPD, the average of the four validators was 90.83%, with very valid criteria. Based on these results, it can be concluded that the development of learning tools based on contextual learning on the subject matter of the set is valid